Exploring the Determinants of Satisfaction and Continuous Intention to Use TVing - Lee, Soo-Jin; Lee, Sun-Kyong (International JOURNAL OF CONTENTS, 2025)
Several factors, including personalization, content diversity, user interface, and cost, wield influence over consumer satisfaction and their enduring commitment to using a platform. This research, centered on TVing, a South Korean Over-the-Top service (also known as streaming service, OTT), aims to unearth the factors that can bolster user satisfaction and mitigate subscriber churn. The study's findings underscore the significant role of personalization and cost in shaping users' expectation confirmation. Moreover, perceived usefulness emerges as a multifaceted construct influenced by all four factors: personalization, content diversity, user interface, and cost. Crucially, the research reveals the interconnectedness of these variables. Expectation confirmation and perceived usefulness are all intrinsically linked to user satisfaction. Higher satisfaction, in turn, yields a greater likelihood of users harboring a continuous intention to utilize the service in the long term. These insights shed light on the complex dynamics governing user interactions with OTT service platforms and offer valuable guidance to service providers like TVing. By understanding and leveraging these factors, platforms can fine-tune their offerings, enhance user experiences, and bolster user retention in a competitive and ever-evolving landscape. KCI Citation Count: 0